Trajectory Tracking Of A Mobile Robot System - Md Ghazaly, Mariam; Abdullah, Zulkeflee; Md Ali, Mohd Amran; Che Amran, Aliza; Chong, Shin Horng (Universiti Teknologi MARA, 2017)
This paper presents an efficient method of mobile robot navigation in an indoor environment. The robot not only helps workers reduce heavy workload, it also protects workers’ physical and mental health from the work-related-stress. However, the navigation of mobile robot in an indoor environment is a challenging task to accomplish due to the requirement to avoid any nearby obstacle during motion. In this paper, the objectives were to design and develop of mobile robot that is able to navigate from one location to another, analyze the accuracy of line following sensor and analyze the trajectory tracking of a mobile robot. In conclusion, the experimental results show that the mobile robot able to reach the target destination successfully without the collision with obstacles, for different types of trajectory patterns using the masking tape width of 18mm with the develop algorithm.